Do Shadow Banking Depositors Discipline the Market? - Vera Intanie Dewi; Nury Effendi; Mokhamad Anwar; Sulaeman Rahman Nidar; Tettet Fitrijanti; Benny Tjandrasa (Australasian Accounting, Business and Finance Journal, 2023)
The shadow banking sector comprises non-bank financial institutions that do not have a deposit guarantee and are barely supervised by the regulator. Efforts to monitor shadow banking must be done well, in both developed and developing countries. Regulators in several countries however have not been fully effective in supervising shadow banking financial institutions, particularly in developing countries such as Indonesia. Therefore, the public's role—in this case, depositors—is essential to supervise shadow banking through the practice of market discipline. However, some factors may cause the market discipline practice to fail, such as low financial literacy. This research aims to examine the influence of financial literacy on the performance of market discipline. This study's research method is a survey of 255 lecturers who have savings accounts in the shadow banking sector in Indonesia. The multivariate analysis method used in this study is partial least squares structural equation modelling (PLS-SEM). This study provides evidence that financial literacy and its variables significantly affect market discipline's effectiveness in shadow banking. By showing that market discipline plays a role in building a sustainable financial ecosystem, this research contributes to depositors, investors, the financial industry, and regulators. Promoting market discipline is an important duty of regulators and other financial institutions. Likewise, promoting financial literacy among depositors and investors, especially in developing countries with low literacy levels, is a challenge to overcome when seeking to create a sustainable financial system.
Keywords: Financial literacy; Market discipline; Shadow banking; Sustainable finance